Autism and intersectionality: Considerations for school-based practitioners - Sassu, Kari A.; Volkmar, Fred R. (Psychology in the Schools, 2022)
The purpose of this article is to explore the intersectionality of autism and sociocultural factors as well as discuss the complexities associated with appropriate assessment, diagnosis, and intervention. Based on a review of the literature, the authors present a brief history of the emergence of the term autism and highlight factors that have contributed to current concerns about failures to appropriately recognize autism within diverse populations. Referencing extant research as well as professional practice standards, this article examines aspects of autism and intersectionality, and explores some of the associated challenges related to assessment, diagnosis, and intervention. Further, the authors reflect on the critical importance of carefully considering all aspects of a child's identity when engaging in autism assessment and intervention within the school setting. School-based practitioners are provided with guidance for addressing the needs of diverse populations of students with autism.
0 citations (Crossref) [2023-10-31] _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/pits.22757
Keywords: SES; autism; dept.csp; dept.sed; ethnicity; intersectionality; peer-reviewed; race